Group Counseling with A Behavioral Approach to Develop Adolescent Life Skills for Mitigating Occupational Health Risks at SMAN 4 Raha - Elna Sari; Rasniah Sarumi; Ayu Naningsih; Endang Sri Mulyawati; Muhammad Suriyadarman Rianse (Poltekita: Jurnal Ilmu Kesehatan, 2025)
Background: In this study, we aimed to evaluate the effectiveness of group counseling with a behavioral approach in preventing risky sexual behavior among adolescents within the context of rising public health concerns in Indonesia. With worrying national trends in premarital sexual activity and STI prevalence among youth, our objective was to assess the impact of a behavioral modification intervention to address gaps in existing school-based preventive programs. Methods: This pre-experimental study involved a one-group pretest-posttest design conducted at SMA Negeri 4 Raha in September 2024. A total of 34 students were enrolled, selected via proportionate stratified random sampling, and data were collected through structured self-administered questionnaires. Ethical approval was obtained from the relevant institutional review board, and participants provided informed assent. Results: The primary outcome of the study was the change in knowledge and awareness scores of safe sexual behavior, and a significant increase from a pre-test mean of 7.94 (SD=2.741) to a post-test mean of 11.44 (SD=3.230) was observed. Statistical analyses revealed a p-value of 0.001, confirming the intervention's significant effect. The findings highlight the effectiveness of group counseling in enhancing adolescent understanding and promoting safer decision-making. Conclusion: In conclusion, our study contributes to the understanding of adolescent sexual health prevention by demonstrating the efficacy of a behavioral group counseling model. This research provides insights into practical, school-based interventions that can be integrated into reproductive health programs. Future studies should address the long-term behavioral outcomes and incorporate a control group design, ultimately advancing knowledge in the field of international adolescent health.